The Influence of Material Storage on Mechanical Properties and Deterioration of Composite Materials - Sara Radojičić; Pejo Konjatić; Marko Katinić; Josip Kačmarčik (Tehnički Vjesnik, 2023)
This article focused on the experimental and statistical analysis of the mechanical properties of dog-bone samples manufactured by fused deposition modelling (FDM). Two identical materials were examined, i.e., Onyx with carbon fiber but from different series and differently stored. One was kept in the manufacturer package and the other one was kept in machine storage box. The paper explains how the samples with various numbers of fiber layers and printing infill were created, 3D printed, measured to evaluate their accuracy in dimensions, exposed to tensile test, and reviewed. At this stage of investigation, the paper is limited to static tests of materials. The data presented here will be of great assistance for additional studies intended for the filament deposition development and modification of the basic material through the combinations with different composites, such as carbon fiber. It was discovered with this research that the mechanical properties of test samples created by FDM can differ based on the manufacturer series. This issue has not been studied thoroughly, so far. Research, by analysing the key variable, which is the batch of 3D print material, offers important new data to engineers and designers. It also prepares the ground for advanced studies and research in respect of the weakness and strength analysis of the 3D printed models.That is very relevant for the optimizing structures in this modern age and the industrial era 4.0 as well as the development in the LEAN process of manufacturing.